Development of exoskeleton finger mechanisms for stroke rehabilitation - Lam, Matthew Jun Wei (Nanyang Technological University, 2024)
Stroke rehabilitation presents various challenges, including limited access to specialized care, lack of intensive rehabilitation options, inconsistent therapy, and variability in therapist exercise. This literature review examines these challenges and proposes a solution aimed at improving rehabilitation outcomes for stroke survivors with curled fingers due to hand spasticity and lack of neuroplasticity. The proposed solution involves developing exoskeleton finger mechanisms specifically designed to address specific needs of individuals with curled fingers post-stroke. These mechanisms aim to provide consistent and intensive rehabilitation options customized to individual needs of stroke patients, thereby addressing identified challenges with stroke rehabilitation. By mitigating these challenges, the project seeks to improve the effectiveness and accessibility of stroke rehabilitation therapeutic services while pushing the boundaries of stroke patient’s recovery potential. The findings of this literature review underscore the importance of targeted interventions in overcoming barriers to optimal stroke recovery and enhancing the overall quality of life for stroke survivors. The overall approach to the design process, design considerations and development of finger mechanisms are covered in the report.